Prosedur Penggajian Pegawai Pada Pusat Penelitian Kelapa Sawit (PKKS) Marihat-Pematangsiantar - Junaidi Junaidi; Ompon Lastiur Sianipar; Sumaizar Sumaizar (SEKOLAH TINGGI AKUNTANSI DAN MANAJEMEN INDONESIA (STAMI), 2020)
Abstract The main role of the system in a company is to help provide clear and orderly procedures for carrying out company operations. The system is needed as a means of monitoring and controlling the course of the company's operational activities in determining every decision. One of the most important management activities in the company is payroll activity. Data collection techniques are interviews and direct observation to the field. Before conducting the interview, an interview document was prepared in the form of a list of questions. The purpose of this study was to analyze the payroll procedures applied in PKKS. The data analysis technique used is the Miles approach where all data is collected and then analyzed and deleted data that does not affect the research until finally verified and drawing conclusions. The payroll system used by the Marihar Business Unit PPKS is a monthly salary/wages system, namely wages within 30 days because this system is considered more effective than other systems.Payment of salaries/wages to all employees is always on time because payments are made via transfer to a designated bank, namely Bank Negara Indonesia Keywords: Operational activities, Payroll, Procedures